ANALISIS SIKAP KONSUMEN TERHADAP PROGRAM CORPORATE SOCIAL RESPONSIBILITY (CSR) BERUPA DONASI PADA BISNIS RITEL ALFAMART - Immanuel Tedjokusumo (Parsimonia - Jurnal Ekonomi dan Bisnis, 2017)
This research aims to analyze the attitudes of consumers regarding the cognitive, affective, and conative components toward Corporate Social Responsibility (CSR) program in the form of Donations Alfamart retail business. This research is a descriptive quantitative research using three box analysis method to measure each component of consumer attitudes toward donation program. This research using a sample of as many as 200 respondents. The results of this study suggest that the cognitive attitude (81,42%), have the highest index which means that consumer knowledge and trust on donation program is very high. Most consumers already know and have felt the benefits of donation program. The affective component is also of high index value (80,3%) which means that consumers feel happy and proud about donating. The conative component shows high index value too (71,1%), but not as high as the cognitive and affective components. This research suggests that PT. SAT (Sumber Alfaria Trijaya) should maintain programs that have been considered the good by community through informing the program via payment receipt, banners and posters which contain the results of the CSR activities that have been carried out in order to help people who are less fortunate.